Linking a econometric model for walking with a land use occupation model to support expansion policies of cities : the case study of Bogotá (2018)
Integrated decision support systems are continually more recognized as important tools in the design and selection of urban expansion policies in the Latin America and the Caribbean cities, in this regard LUCC models have been adapted recently in rapid growing cities such as Bogotá. This study developed a travel behaviour model for walking with a land use component among the independent variables. The model serves to estimate walking distances according to the socioeconomic profile of an individual but also contemplates the near environment surrounding their neighbourhood, so a link with the LUCC model is straight forward. The main objective of this research was to estimate the effects of future land use change in walking as a mean of transport. For this purpose, three core stages were proposed, first a travel behaviour econometric model with a land use mix factor was specified. Then in a second stage a LACC model was run in order to obtain two scenarios of future...